Pengaruh Kompensasi, Motivasi Dan Loyalitas Karyawan Terhadap Kinerja Karyawan Pada Lombok Post Group Mataram - Sahar Sahar; Resky Setiawati (Fakultas Ekonomi Universitas Islam Al-Azhar, 2019)
This study aims to examine the effect of compensation, motivation and employee loyalty on employee performance. So that this research variable consists of 3 (three) independent variables namely compensation (X1), motivation (X2), and employee loyalty (X3) and the dependent variable is employee performance (Y). The population of this research is Lombok Post Mataram employees who are involved in the company. This type of research used in this research is associative research. Samples were taken using purposive sampling where employees were made into a sample of 36 people. Data obtained by crossing 36 questionnaires on respondents in the Lombok Post Mataram. Data were analyzed using multiple linear regression. The results show that employee compensation, motivation and loyalty have a significant effect on employee performance as evidenced by the regression coefficient value Y = 2.458 + 0.340X1 + 0.241X2 + 0.592X3. The results of this study also show that compensation (X1), motivation (X2) and employee loyalty (X3) simultaneously have a significant effect on employee performance (Y) with a calculated F value> F table (86.521> 2.90) and an Adjusted R Square of 0.880. Through t test analysis, each variable x has t arithmetic> t table, namely compensation (2,357> 2,034) motivation (2,156> 2,034) and loyalty (4,565> 2,034). And loyalty variable is the most dominant variable influencing employee performance (Y) which is indicated by the highest beta coefficient value that is equal to 0.592.